Measurement of CP asymmetries in two-body B0(s)-meson decays to charged pions and kaons - Aaij, Roel; D'Argent, Philippe; Bachmann, Sebastian; Berninghoff, Daniel; Braun, Svende; De Cian, Michel; Comerma-Montells, Albert; Dordei, Francesca; Dziewiecki, Michal; Gerick, David; Grabowski, Jascha; Han, Xiaoxue; et al. (Physical review, 2018)
The time-dependent CP asymmetries in B0→π+π− and B0s→K+K− decays are measured using a data sample of p p collisions corresponding to an integrated luminosity of 3.0 fb−1, collected with the LHCb detector at center-of-mass energies of 7 and 8 TeV. The same data sample is used to measure the time-integrated CP asymmetries in B0→K+π− and B0s→π+K− decays. The results are Cπ+π−=−0.34±0.06±0.01, Sπ+π−=−0.63±0.05±0.01, CK+K−=0.20±0.06±0.02, SK+K−=0.18±0.06±0.02, AΔΓK+K−=−0.79±0.07±0.10, AB0CP=−0.084±0.004±0.003, and AB0sCP=0.213±0.015±0.007, where the first uncertainties are statistical and the second systematic. Evidence for CP violation is found in the B0s→K+K− decay for the first time.
Im Titel sind "0" und "(s)" untereinander geschrieben: "0" hochgestellt, "(s)" tiefgestellt
LHCb collaboration: R. Aaij, P. d'Argent, S. Bachmann, D. Berninghoff, S. Braun, A. Comerma-Montells, M. De Cian, F. Dordei, M. Dziewiecki, D. Gerick, J.P. Grabowski, X. Han, S. Hansmann-Menzemer, M. Kecke, B. Khanji, M. Kolpin, R. Kopecna, B. Leverington, J. Marks, D.S. Mitzel, S. Neubert, M. Neuner, A. Piucci, M. Stahl, S. Stemmle, J. van Tilburg, U. Uwer, A. Zhelezov [und weitere] (LHCb collaboration)
Gesehen am 30.04.2019